Mechanical properties of heat-treated duplex electroless nickel coatings. (1st February 2019) - Vitry, Veronique; Francq, Elodie; Bonin, Luiza
ABSTRACT: Electroless nickel coatings present complementary properties: coatings formed using hypophosphite present usually better corrosion resistance while those made with borohydride present better mechanical and wear properties. Duplex coatings, combining both kinds of deposits, are designed to combine features of both nickel–phosphorus (ENP) and nickel–boron (ENB) coatings. In this study, monolayer and bilayer coatings were synthesised on mild steel substrates, in various combinations of ENP and ENB, with a total thickness of 20 µm and heat treated (400°C – 1 h) under non-reactive atmosphere (95% Ar–5% H2 ) to enhance their mechanical properties. The morphology, roughness, hardness, abrasive wear resistance and scratch behaviour of the coatings were investigated. Samples with ENP as the top layer showed a higher roughness than samples with ENB as the external layer. However, samples with ENB as the top layer provided better wear resistance, even if they presented a lower combined hardness. ENB monolayer showed the best resistance to scratch testing.